Pengaruh Kemudahan Penggunaan, Gaya Hidup, Persepsi Keamanan Dan Kepercayaan Terhadap Minat Menggunakan Shopeepay - Gine Das Prena; Ni Kadek Sri Gayatri Dewi (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Using digital wallets has become a lifestyle, especially for millennials. The existence of popular applications such as Shopee, Gojek, Traveloka, Grab, Ovo, Link Aja and Ruang Guru also makes the intensity of application use on smartphones increase. All of these applications require a fast and concise payment system. For this reason, the role of digital wallets is felt to be increasingly important today. The purpose of this study is to determine the effect of Ease of Use, Lifestyle, Security Perception and Trust on Public Interest in Using Shopeepay. The method that the author uses in this study is quantitative data method, then the data is processed with Multiple Linear Regression Analysis method using the help of SPSS version 22 for Windows. The sample used in this study was 100 samples of the millennial generation in the city of Denpasar through the distribution of questionnaires. Simultaneous or partial results of ease of use, lifestyle, perceived security, and trust have a positive influence on interest in using shopeepay.